2016
DOI: 10.1002/cnma.201600131
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Approach to Covalently Functionalized Graphene Nanosheet Hybrids and Polymer Nanocomposites

Abstract: Homogeneousd ispersion and ag ood interface between polymer and filler is crucial to obtain high-performance polymer composites. In this work, we use an ovel method employing organic aminopropyl-functionalized nanosilica sols (OAS-sols) to functionalize graphene oxide (GO) and thereby synthesize OAS covalently grafted graphene hybrid nanosheets (OAS-graphene). The spherical OAS covalently attached on the two-dimensional (2D) nanosheet GO surfaces creates OAS-graphene hybrids, which have large surface areas and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…They found that the flexural strength and impact strength of 10 wt% fillers filled the composites increased by 20% and 28%, respectively. Fu et al . reported the flexural modulus and impact strength of OAS‐graphene/epoxy nanocomposites were enhanced by 32.8% and 76.3%, respectively at 1.5 wt% loading.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the flexural strength and impact strength of 10 wt% fillers filled the composites increased by 20% and 28%, respectively. Fu et al . reported the flexural modulus and impact strength of OAS‐graphene/epoxy nanocomposites were enhanced by 32.8% and 76.3%, respectively at 1.5 wt% loading.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the amino groups can further boost the interfacial heat transfer because amino groups react chemically with epoxy resin and bond graphene to epoxy resin covalently. , Another contribution of functionalization is preventing the aggregation of graphene in the epoxy resin matrix, facilitating graphene to form the three-dimensional network under lower concentrations . Fu et al employed aminopropyl to modify graphene oxide experimentally for better graphene dispersion. The composite’s thermal conductivity increased by 74.13% with a graphene concentration of 1.5 wt %.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6 Therefore, many researchers have focused on the development of epoxy-based composite materials that have high thermal conductivities but are electrically insulating. 3,7 Melt and solution mixing are common methods for enhancing the thermal conductivity of a polymer and are used to introduce a large amount of thermally conductive fillers, such as graphite, [8][9][10] carbon nanotubes, 11,12 metallic powders, 13 boron nitride (BN), 14,15 or aluminum nitride. 16 However, polymer-based thermally conductive composites prepared by these methods typically have a random distribution of filler particles.…”
Section: Introductionmentioning
confidence: 99%